Local Sleep Slow-Wave Activity Colocalizes With the Ictal Symptomatogenic Zone in a Patient With Reflex Epilepsy: A High-Density EEG Study - Moffet, Eric W.; Verhagen, Ruben; Jones, Benjamin; Findlay, Graham; Juan, Elsa; Bugnon, Tom; Mensen, Armand; Aparicio, Mariel Kalkach; Maganti, Rama; Struck, Aaron F.; Tononi, Giulio; Boly, Melanie (Frontiers in Systems Neuroscience, 2020)
Slow-wave activity (SWA) during non-rapid eye movement (NREM) sleep reflects synaptic potentiation during preceding wakefulness. In animal studies seizures induce synaptic potentiation; SWA is a marker of synaptic strength, therefore, epileptic activity may also induce increases in state-dependent SWA in human brains. We analyzed high-density EEG (HDEEG) data across vigilance states from a reflex epilepsy patient with a clearly localizable ictal focus to provide a proof-of-concept for the testability of this hypothesis. Overnight HDEEG recordings were obtained in the patient during various vigilance states - REM sleep, NREM sleep, wakefulness, and during a right facial motor seizure - and compared to 10 controls. After preprocessing, SWA (1-4 Hz, delta power) was calculated at each channel. Scalp level and source reconstruction analyses were computed. Statistics assessed for differences in maximum SWA in patient versus controls during each vigilance state, and within each state minus REM sleep. Topographical analysis revealed greater left hemispheric SWA in the patient versus controls in all vigilance states except REM sleep. Source space analysis revealed increased SWA in the left inferior frontal cortex during NREM sleep and wakefulness. Ictal data displayed poor source-space localization. Comparing each state to REM sleep enhanced localization accuracy; the most clearly localizing results were observed when subtracting REM sleep from wakefulness. State-dependent SWA help to identify epileptic foci. These results support the hypothesis that epileptic activity may induce synaptic potentiation in the human brain. Future work in larger cohorts may assess the clinical value of sleep SWA to help presurgical planning.